2021
DOI: 10.1007/s11162-021-09634-y
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Cost Efficiency at Public Community Colleges in the US: A Stochastic Frontier Analysis

Abstract: This study utilizes an extensive panel data set spanning 15 years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) and 752 public community colleges to investigate operating costs and persistent cost efficiency at public community colleges in the United States. We employ a generalized true random effects (GTRE) regression model that takes into account spatial correlation of costs among community colleges, to estimate cost efficiency via stochastic frontier analysis (SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The model used in this study was the SFA translog multiproduct cost frontier, suggested by Agasisti (2016) and Kumbhakar & Knox (2000). The translog function has a higher degree of flexibility and is often used to analyze efficiency in public higher education establishments (see Fahmy-Abdullah et al, 2021;Ferro & D'elia, 2020;Giraleas, 2021;Gralka, 2018a;Titus et al, 2021;Vamosiu et al, 2018). In 2021, based on data from the Ministry of Education, Culture, Research, and Technology, there were 68 public higher education establishments in Indonesia.…”
Section: Research Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The model used in this study was the SFA translog multiproduct cost frontier, suggested by Agasisti (2016) and Kumbhakar & Knox (2000). The translog function has a higher degree of flexibility and is often used to analyze efficiency in public higher education establishments (see Fahmy-Abdullah et al, 2021;Ferro & D'elia, 2020;Giraleas, 2021;Gralka, 2018a;Titus et al, 2021;Vamosiu et al, 2018). In 2021, based on data from the Ministry of Education, Culture, Research, and Technology, there were 68 public higher education establishments in Indonesia.…”
Section: Research Methods and Datamentioning
confidence: 99%
“…The input data were obtained from the performance reports of the public higher education providers in 2021. The use of total expenditure in the cost frontier has been applied by many researchers to model SFA (Agasisti & Gralka, 2019;D'elia & Ferro, 2021;Fu et al, 2019;Titus et al, 2021;Vamosiu et al, 2018).…”
Section: Ci=c(y(k)i)mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the stochastic frontier model (SFA) and the Solow residual method (SRA) are used as parametric analysis methods to derive efficiency results primarily through modeling and variable assumptions [44]. For example, Titus et al [45] calculated the resource allocation of 752 community colleges in the US with the help of the SFA model and found a high level of overall efficiency. Song Zhiyan et al [46] used the SFA model to calculate the input-output efficiency of general universities in China and concluded that the overall efficiency profile was good, but there were internal gaps and input redundancy.…”
Section: Resource Allocation Efficiency Evaluation Methodsmentioning
confidence: 99%
“…Despite the relatively small size of average institutions, they found that economies of scale are largely exhausted. Titus, Vamosiu, Buenaflor and Lukszo (2021) used an extensive panel data set spanning 15 years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) and 752 public community colleges to investigate operating costs and persistent cost efficiency at public community colleges in the United States and revealed a positive relationship between operating costs and associate degrees and certificates as well both human (part and full-time faculty) and financial resources (local, state and federal funding and tuition revenue), controlling for other variables. They observed an average persistent (long-term) efficiency of 87% while few institutions were relatively cost inefficient.…”
Section: Literature Reviewmentioning
confidence: 99%